Strain variation in the infectivity of Schistosoma mansoni for Biomphalaria glabrata - Luiz Candido de Souza Dias; John I. Bruce; Gerald C. Coles (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
Five strains of Schistosoma mansoni resistant and susceptible to schistosomicides were studied for infectivity of 2 strains of Biomphalaria glabrata one of Puerto Rican origin and the other of Brazilian origin. Puerto Rican strains of S. Mansoni developed more slowly and had a lower infectivity in Brazilian B. glabrata than did the Brazilian S. mansoni. However, Brazilian S. Mansoni developed as well in Puerto Rican snails as in Brazilian snails, indicating that drug resistant strains could easily be moved by travel of infected persons from one area to another.